Pengaruh Job Insecurity Terhadap Kinerja Karyawan Outsourcing Business Support Melalui Motivasi Sebagai Variabel Intervening Pada Pt. Telekomunikasi Selular Cabang Medan - Nuri Aslami (Jurnal Manajemen Dan Akuntansi Medan, 2019)
PT. Telekomunikasi Selular is a company engaged in the mobile telecommunications business industry in Indonesia. The company uses outsourcing employees for several positions, one of which is the administrative position to support of the company activities. The purpose of this research is to 1) analyze the influence of job insecurity on the motivation of employee outsourcing business support at PT. Telekomunikasi Selular Branch Medan; 2) analyze the influence of job insecurity on the performance of employee outsourcing business support at PT. Telekomunikasi Selular Branch Medan; 3) analyze the influence of motivation on the performance of employee outsourcing business support at PT. Telekomunikasi Selular Branch Medan; 4) analyze the influence of job insecurity on the performance of employee outsourcing business support through motivation as intervening variable at PT. Telekomunikasi Selular Branch Medan. Population in this research is employee outsourcing PT. Telkomsel Medan Branch which has 132 people with a sample of 99 people. The engineering samples used in this research is Simple Random Sampling technique. Data analysis method used is path analysis. The results showed that 1) Job insecurity has a negative and significant impact on the motivation of employee outsourcing bussiness support at PT. Telkomsel Branch Medan. 2) Job insecurity has a negative and significant impact the performance of employee outsourcing bussiness support at PT. Telkomsel Branch Medan. 3) Motivation has a positive and significant impact on the performance of employee outsourcing bussiness support at PT. Telkomsel Branch Medan. 4) Job insecurity has a negative and significant impact on the performance of employee outsourcing bussiness support through work motivation at PT. Telkomsel Branch Medan.